Management of productive capital of cognac industry enterprises of Ukraine - Mohylova, A.Y. (Економіка промисловості, 2014)
Substantiated that the structure of capital involved is the determining factor for predicting capitalization Odessa Cognac Factory. For this reason, to ensure capitalization of the enterprise of cognac industry in Ukraine should focus on the management of development and utilization of productive capital, which is based on planting grapes. In the article the new approach to assessing capitalization of enterprise complete cycle of cognac through organizational and economic transformation of the production capital as a resource base for future capitalization. Focusing on the importance of the sugar content of grapes figure for the volume of alcohol, all calculations are carried out for reasons of ensuring the most collected large amounts of sugar. On this basis concluded that the possible optimization potential distribution area of land under vine particular brand. Given the optimal allocation structure planting grapes for the production of cognac alcohol at Odessa Cognac Factory «Shustov» medium duty sugar harvest grapes can be increased by 3,7%. However, EBITDA increased by 27,8%. Growth of EBITDA ratio can be interpreted as increased capitalization of the test plant. Thus, the redistribution of land area between the grape varieties are output by improving operational performance through better use of the available productive capacity. Доведено, що для забезпечення капіталізації підприємства коньячної галузі України варто зосередити увагу на управлінні процесом формування та використання виробничого капіталу. Обґрунтовано новий підхід до оцінки капіталізації підприємства повного циклу виробництва коньяку через організаційно-економічні трансформації виробничого капіталу як ресурсної основи майбутньої капіталізації. Доказано, что для обеспечения капитализации предприятия коньячной отрасли Украины следует сосредоточить внимание на управлении процессом формирования и использования производственного капитала. Обоснован новый подход к оценке капитализации предприятия полного цикла производства коньяка через организационно-экономические трансформации производственного капитала как ресурсной основы будущей капитализации.